α-Actinin-4 Promotes the Progression of Prostate Cancer Through the Akt/GSK-3β/β-Catenin Signaling Pathway - Park, Sungyeon; Kang, Minsoo; Kim, Suhyun; An, Hyoung-Tae; Gettemans, Jan; Ko, Jesang (Frontiers in Cell and Developmental Biology, 2020)
The first-line treatment for prostate cancer (PCa) is androgen ablation therapy. However, prostate tumors generally recur and progress to androgen-independent PCa (AIPC) within 2–3 years. α-Actinin-4 (ACTN4) is an actin-binding protein that belongs to the spectrin gene superfamily and acts as an oncogene in various cancer types. Although ACTN4 is involved in tumorigenesis and the epithelial–mesenchymal transition of cervical cancer, the role of ACTN4 in PCa remains unknown. We found that the ACTN4 expression level increased during the transition from androgen-dependent PCa to AIPC. ACTN4 overexpression resulted in enhanced proliferation and motility of PCa cells. Increased β-catenin due to ACTN4 promoted the transcription of genes involved in proliferation and metastasis such as CCND1 and ZEB1. ACTN4-overexpressing androgen-sensitive PCa cells were able to grow in charcoal-stripped media. In contrast, ACTN4 knockdown using si-ACTN4 and ACTN4 nanobody suppressed the proliferation, migration, and invasion of AIPC cells. Results of the xenograft experiment revealed that the mice injected with LNCaPACTN4 cells exhibited an increase in tumor mass compared with those injected with LNCaPMock cells. These results indicate that ACTN4 is involved in AIPC transition and promotes the progression of PCa.